Mortality from mental disorders and suicide in male professional American football and soccer players: A meta-analysis - Morales, J. S.; Castillo-García, A.; Valenzuela, P. L.; Saco-Ledo, G.; Mañas, A.; Santos-Lozano, A.; Lucia, A. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Objective: To determine the risk of mortality from mental disorders and suicide in professional sports associated with repeated head impacts. Methods: A systematic search was performed in PubMed, Web of Science, Scopus, and SPORTDiscus (since inception to June 8, 2021) to find studies comparing the incidence of mortality from mental disorders or suicide in former or active professional athletes of sports characterized by repeated head impacts vs athletes with no such exposure or the general non-athletic population. Results: Seven retrospective studies of moderate-to-high quality that included data from boxers and from basketball, ice hockey, soccer, and National Football League (NFL) players, respectively (total = 27 477 athletes, 100% male) met all inclusion criteria. Former male NFL players (n = 13 217) had a lower risk of mortality from mental disorders (standard mortality rate [SMR] = 0.30; 0.12-0.77; p = 0.012) and suicide (SMR = 0.54; 0.37-0.78; p < 0.001) than the general population. This finding was also corroborated in male soccer players (n = 13,065; SMR = 0.55; 0.46-0.67; p < 0.001). Male athletes participating in sports associated with repeated head impacts (n = 18,606) had also a lower risk of all-cause, cardiovascular disease (CVD), and cancer mortality (all p < 0.01) than the general population. Conclusions: Participation of male athletes in American football or soccer at the professional level might confer a certain protective effect against mortality from mental disorders or suicide, besides its association with a lower risk of all-cause, CVD, or cancer-related mortality.